2015
DOI: 10.1111/imm.12518
|View full text |Cite
|
Sign up to set email alerts
|

Topical steroid therapy induces pro‐tolerogenic changes in Langerhans cells in human skin

Abstract: We have investigated the efficacy of conditioning skin Langerhans cells (LCs) with agents to promote tolerance and reduce inflammation, with the goal of improving the outcomes of antigen-specific immunotherapy. Topical treatments were assessed ex vivo, using excised human breast skin maintained in organ bath cultures, and in vivo in healthy volunteers by analysing skin biopsies and epidermal blister roof samples. Following topical treatment with a corticosteroid, tumour necrosis factor-α levels were reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In terms of the pathological mechanisms, glucocorticosteroids are known to suppress immune pathways in keratinocytes and to negatively affect the viability, maturation, and immune function of inflammatory cells [ 17 , 18 ]. In addition, recent findings have shown that topical steroids may achieve anti-inflammatory effects and contribute to reduced numbers of fibroblasts [ 19 , 20 ]. The lesion in UG is characterized by overgrowth of granulation tissue after umbilical cord separation.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the pathological mechanisms, glucocorticosteroids are known to suppress immune pathways in keratinocytes and to negatively affect the viability, maturation, and immune function of inflammatory cells [ 17 , 18 ]. In addition, recent findings have shown that topical steroids may achieve anti-inflammatory effects and contribute to reduced numbers of fibroblasts [ 19 , 20 ]. The lesion in UG is characterized by overgrowth of granulation tissue after umbilical cord separation.…”
Section: Discussionmentioning
confidence: 99%
“…Topical steroid therapy can modulate the Langerhans cells in the human skin through inhibiting proinflammatory signals and enhancing tolerance 18 . For example, cytokines, such as TNF-α and IL-1β, have been reported to decrease on the ocular surface following application of topical steroids 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the release of proinflammatory cytokines was reduced by this drug in DCs. Betamethasone has been reported to induce tolerogenic Langerhans DCs (LDCs) in the skin of patients with psoriasis ( 47 ) and atopic dermatitis, which in turn arrest T helper (Th) 1 and Th2 responses ( 48 ). Similarly to the effects found in monocytes, human DCs differentiated with betamethasone showed a reduction of membrane expression of costimulatory molecules, such as CD40 and CD86, accompanied by a decrease in IL-12 secretion, an important cytokine for Th1 responses.…”
Section: Direct Effects Of Betamethasone On the Immune Systemmentioning
confidence: 99%